Enhanced catalytic conversion of palm oil into biofuels by Cr-incorporated sulphated zirconia - Utami, Maisari; Safitri, Resti; Pradipta, M. Fajar; Wijaya, Karna; Chang, Soon Woong; Ravindran, Balasubramani; Ovi, Debnath; Rajabathar, Jothi Ramalingam; Poudineh, Neda; Gengan, Robert Moonsamy (Elsevier B.V., 2021)
The conversion of palm oil into biofuels using commercial zirconia (ZrO2) modified sulfuric acid (H2SO4) incorporated with Cr metal has been systematically studied. Sulphated zirconia (ZrO2-SO4) was prepared by dispersing ZrO2 in H2SO4 solution via wet impregnation method. Cr-incorporated sulphated zirconia (Cr/ZrO2-SO4) were prepared hydrothermally through wet impregnation of ZrO2-SO4 and chromium (III) nitrate nonahydrate (Cr(NO3)3·9H2O) solution. The results showed that reduction step with pure hydrogen gas (H2) over non-calcined catalyst (Cr/ZrO2-SO4 (NC)) resulted in higher activity and selectivity than calcined catalyst (Cr/ZrO2-SO4 (C600)). A maximum acidity test result was obtained on Cr/ZrO2-SO4 (NC) of 2.33 mmol g−1, increasing from Cr/ZrO2-SO4 (C600) of 1.32 mmol g−1. The selectivity of gasoline fraction demonstrated by Cr/ZrO2-SO4 (C600) and Cr/ZrO2-SO4 (NC) was observed to contain 35.85% and 36.51%, respectively.